Linking lifestyle and foraging strategies of marine bacteria: selfish behaviour of particle‐attached bacteria in the northern Adriatic Sea. Issue 4 (31st March 2022) - Manna, Vincenzo; Zoccarato, Luca; Banchi, Elisa; Arnosti, Carol; Grossart, Hans‐Peter; Celussi, Mauro
Summary: Microbe‐mediated enzymatic hydrolysis of organic matter entails the production of hydrolysate, the recovery of which may be more or less efficient. The selfish uptake mechanism, recently discovered, allows microbes to hydrolyze polysaccharides and take up large oligomers, which are then degraded in the periplasmic space. By minimizing the hydrolysate loss, selfish behaviour may be profitable for free‐living cells dwelling in a patchy substrate landscape. However, selfish uptake seems to be tailored to algal‐derived polysaccharides, abundant in organic particles, suggesting that particle‐attached microbes may use this strategy. We tracked selfish polysaccharides uptake in surface microbial communities of the northeastern Mediterranean Sea, linking the occurrence of this processing mode with microbial lifestyle. Additionally, we set up fluorescently labelled polysaccharides incubations supplying phytodetritus to investigate a 'pioneer' scenario for particle‐attached microbes. Under both conditions, selfish behaviour was almost exclusively carried out by particle‐attached microbes, suggesting that this mechanism may represent an advantage in the race for particle exploitation. Our findings shed light on the selfish potential of particle‐attached microbes, suggesting multifaceted foraging strategies exerted by particle colonizers.